Perbandingan Rasa, Harga, Dan Kenyamanan Kudapan Surabi Di Jalan Setiabudi - Aloysius Benedict Rafael; Ryan Hadi Syaputra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to compare three main aspects of the experience of enjoying traditional Surabi snacks in a number of places along Jalan Setiabudi, Bandung, namely taste, price, and comfort. The method used is a qualitative descriptive approach with observation, interview, and survey techniques to consumers. The results of the study show that there is a significant variation in the taste of Surabi offered by culinary business actors, both in terms of texture, sweetness level, and the peculiarity of toppings. In terms of price, it was found that differences do not always reflect the quality of taste, but are also influenced by location and market segmentation. The comfort of the dining place, including cleanliness, atmosphere, and supporting facilities, is an important factor in determining consumer preferences, especially young people and tourists. These findings can be a reference for culinary MSME actors in improving competitiveness and service quality, as well as providing practical information for consumers in choosing a place to enjoy Surabi that suits their needs and tastes.